2015
DOI: 10.1016/j.ultsonch.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Modification of foaming properties of soy protein isolate by high ultrasound intensity: Particle size effect

Abstract: The effect of high intensity ultrasound (HIUS) may produce structural modifications on proteins through a friendly environmental process. Thus, it can be possible to obtain aggregates with a determined particle size, and altering a defined functional property at the same time. The objective of this work was to explore the impact of HIUS on the functionality of a denatured soy protein isolate (SPI) on foaming and interfacial properties. SPI solutions at pH 6.9 were treated with HIUS for 20 min, in an ultrasonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(85 citation statements)
references
References 34 publications
(32 reference statements)
3
76
1
5
Order By: Relevance
“…Furthermore, the high intensity ultrasound (HIUS) treatment and HIUS with temperature improved the foaming capacity by alteration of particle size whereas stability was not modified significantly (Morales et al . ). The temperature of HIUS treatment (80C and 85C) show a synergistic effect on foaming capacity, and the reduction of particle size was related to the increase of foaming capacity of SPIs.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, the high intensity ultrasound (HIUS) treatment and HIUS with temperature improved the foaming capacity by alteration of particle size whereas stability was not modified significantly (Morales et al . ). The temperature of HIUS treatment (80C and 85C) show a synergistic effect on foaming capacity, and the reduction of particle size was related to the increase of foaming capacity of SPIs.…”
Section: Resultsmentioning
confidence: 97%
“…Time of sonication was selected conforming previous studies at different times [7] and was chosen the time where more pronounced was the HIUS effect on foaming properties.…”
Section: High-intensity Ultrasound (Hius) Treatmentmentioning
confidence: 99%
“…It may cause physical changes on proteins producing aggregates through non-covalent bonds by cyclic generation and collapse of cavities depending of structural and protein state aggregation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently particles including hydrogel protein particle, capsules, protein aggregates and polymer fibres etc. have received considerable attention [45][46][47][48][49], which could be promising in application of foods and drug delivery mediums. These particles would greatly extend the types of particles that can influence the thin film properties which are so important to the foam stabilisation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the presence of aggregates can have a large influence on foam stability of protein solutions [42]. Whey protein aggregates [36,37,43], soy protein aggregates [44,45] whey protein fibrils [38,46] and whey protein microgel [47,48] were shown to be advantageous for foam stabilization, while other studies indicated that protein aggregates can also decrease foam stability [41,43]. The aggregate size resulting in higher foam stability varied for different aggregated materials and their structure [41,43].…”
Section: Foams Stabilized By Mixed System Of Protein and Aggregatesmentioning
confidence: 99%